Cephalops Fallén and Semicephalops De Meyer (Diptera: Pipunculidae) of Colombia, with description of five new species and an updated key to males of the Neotropical species - Ramos-Pastrana, Yardany; Marques, Dayse Willkenia A.; Rafael, José Albertino (Zootaxa, 2022)
The pipunculid genera Cephalops Fallén, 1810 and Semicephalops De Meyer, 1994 are cosmopolitan in distribution. These two genera have just a few species known from the Neotropical Region and they were completely unknown to Colombia. Four new species of Cephalops and one species of Semicephalops are described from protected areas and conflict-territories of limited access in Colombia, namely Cephalops acutus sp. nov. (type locality: Cañaveral, Magdalena), C. gracilis sp. nov. (type locality: El Níspero, Boyacá), C. klinsmanni sp. nov. (type locality: Las Brisas, Caquetá), C. lobatus sp. nov. (type locality: El Níspero, Boyacá) and Semicephalops folium sp. nov. (type locality: Quebrada Carrizal, Boyacá). With this paper, the number of Cephalops species from the Neotropical Region increase from 13 to 17 and that of Semicephalops from five to six. Cephalops amapaensis Rafael, 1990 and Semicephalops inpaganus Rafael, 1990 are recorded for the first time from Colombia, and amended diagnosis are provided for both. A dichotomic key to the Neotropical species of both genera is presented.